Percutaneous Coronary Sinus-Based Mitral Valve Repair Differentially Modulates Coronary Sinus to Mitral Valve Annulus Geometry and Topography - Rottländer, Dennis; Saal, Martin; Gödde, Miriel; Ögütcü, Alev; Degen, Hubertus; Haude, Michael (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Coronary sinus (CS) based mitral annuloplasty using the Carillon device is a therapeutic option for the treatment of functional mitral valve regurgitation (FMR). Background: Little is known about the change of CS and mitral valve annulus (MVA) planes following Carillon implantation and how they are modulated by the tension applied on the device. Methods: In a retrospective single-center analysis, 10 patients underwent Carillon device implantation and received CT-angiography (CTA) prior and post CS based percutaneous mitral valve repair. Patients were assigned to responders or non-responders according to the 3-month transthoracic echocardiographic follow-up. A prototype software was used to assess distance and angulation of both CS (pre) or Carillon-device (post) and mitral annulus planes. Results: Comparison of the distance and angulation of the CS plane or Carillon device plane and the MVA plane prior and post intervention showed significant reduction of distance and unchanged angulation in responders while angulation was increased and distance reduced in non-responders without statistical significance. Furthermore, in FMR responders MVA perimeter, anterior-posterior diameter, intercommisural diameter and MVA area were decreased following successful indirect mitral valve annuloplasty, while in FMR non-responders Carillon device implantation had no effect on MVA geometry. Conclusions: Insufficient reduction of FMR following indirect mitral valve annuloplasty is associated with device malposition in relation to the mitral valve annulus. Patient selection using CTA-derived distance and angulation of CS to MVA planes is one option to increase effectiveness of indirect mitral valve annuloplasty.